PENERAPAN ICE BREAKING DALAM PENUMBUHAN MOTIVASI BELAJAR PADA KELAS V MADRASAH IBTIDAIYAH GUPPI CININI INDRAMAYU - Arif Rahman Sholeh; Abdur Rahim (Bajang Institute, 2022)
This research was carried out because of a sense of boredom when learning became monotonous because many students are not focused on learning and needed a short-lived entertainment to foster a spirit of learning. This study aims to get the results of the application of ice breaking to learning and find out whether ice breaking can motivate students in learning thus Teaching and Learning Activities (KBM) become active and fun. This study used qualitative research and simulation approaches. Data collection techniques were carried out in 4 ways, namely: 1) observation, 2) interviews, 3) tests, and 4) documentation. The objects of this research were ice breaking and students. Mathematics is a subject in this research therefore; it makes pre-test and post-test data collection. Based on the results of the application of ice breaking in growing motivation to learn, in this study showed an increase in the value of the average assessment of the first question of 61.90 and the second assessment of 72.62 with an increase in value of 10.72. This means that ice breaking can foster student-learning motivation in class V MI GUPPI Cinini, so it is beneficial for teachers to overcome monotonous classes.